Democracy and the Political Good Problem in Modernity: An Analytical Consideration via the Perspectives of Fukuyama, Calli - Puanghut, Chetta (Journal of Social Sciences Naresuan University, 2019)
The author, in this article, aims to explore and assess the debate about the significance of the transformations taking place across Eastern Europe during 1989-1991, especially in the Soviet Union, by raising a series of questions which needs clarification, including whether the Western ideology has finally triumphed, whether liberal democracy has really conquered rival ideologies and whether ideological conflict has actually come to an end. He believes that the 1989 debate is not merely a debate about events of that year and other events that followed but the debate on modernity. He takes into account, in this article, a series of analytical problems arising from such a debate and tries to point out that the conceptualisation of the political good remains, until now, controversial especially via the perspectives of Fukuyama, Callinicos and Giddens. He concludes, in the final part of this article, that the debate on the political good has become one of the debates concerning the nature and the significance of democracy which seems more and more vivid since the 1989 event.